THE INFLUENCE OF IMAGE MEDIA ON STUDENTS' SPEAKING SKILLS IN ENGLISH - Moh. Andika Wahyu Utama (The Ellite of Unira, 2019)
The formulation of the problem in this study is whether the use of image media has an effect on learning the ability to speak English in English?In this study a total sample of 24 students was applied. The instruments in this study were Pre-Test and Post-Test. Data analysis used descriptive analysis and inferential statistical analysis with the help of computers using the Statistical Package for Social Science (SPSS) Version 25 program.The results of the study can be concluded that 1) the ability to tell students before using the media images in class X IPA 4 MA Negeri Sampang students are generally categorized as very low and unable. The average value obtained by students only touches on the number 46.33.2) the students' ability to tell stories after using the picture media in class X IPA 4 MA Negeri Sampang students are generally categorized as being moderate or capable. This is evidenced by the average value obtained by students touching the number 71.67. 3) the effect of learning the ability to tell stories in class X IPA 4 MA Negeri Sampang shows that there is a significant difference of 0,000 less than the significance of 0.05 (0,000 <0.05), then the hypothesis (Ha) in this study is accepted. This means that the variable use of image media has an effect on student learning outcomes, there is a significant effect between the students' ability to tell stories before using the media and after using the media images in class X IPA 4 MA Negeri Sampang students.